1999
DOI: 10.1103/physrevlett.82.4866
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Oxidation of Aluminum Nanoclusters using Variable Charge Molecular-Dynamics Simulations on Parallel Computers

Abstract: Oxidation of aluminum nanoclusters is investigated with a parallel molecular-dynamics approach based on dynamic charge transfer among atoms. Structural and dynamic correlations reveal that significant charge transfer gives rise to large negative pressure in the oxide which dominates the positive pressure due to steric forces. As a result, aluminum moves outward and oxygen moves towards the interior of the cluster with the aluminum diffusivity 60% higher than that of oxygen. A stable 40 Å thick amorphous oxide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
232
3
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 322 publications
(256 citation statements)
references
References 22 publications
20
232
3
1
Order By: Relevance
“…[44] techniques are available, but only selected publications are used here for comparison since the specification whether or not the sample material was oxygen saturated is crucial. Our samples are assumed to be oxygen saturated as the oxygen contamination of the surface is practically inevitable unless enormous effort is expended in the preparation of the experiment (e.g., vacuum transfer chamber) since a nanometer-thick oxide layer [42] will form immediately after exposure of the sample to regular air. Mills [25] data, based on a literature review by Keene, [43] have been suggested to represent oxygen saturated aluminum.…”
Section: F Surface Tensionmentioning
confidence: 99%
“…[44] techniques are available, but only selected publications are used here for comparison since the specification whether or not the sample material was oxygen saturated is crucial. Our samples are assumed to be oxygen saturated as the oxygen contamination of the surface is practically inevitable unless enormous effort is expended in the preparation of the experiment (e.g., vacuum transfer chamber) since a nanometer-thick oxide layer [42] will form immediately after exposure of the sample to regular air. Mills [25] data, based on a literature review by Keene, [43] have been suggested to represent oxygen saturated aluminum.…”
Section: F Surface Tensionmentioning
confidence: 99%
“…Oxidation of Al nanoclusters [19,20] or single-crystal surfaces of Al [21,22] for pressure ranging from 10 to 40 times the normal state were studied by variable charge molecular dynamics (VCMD) approaches. Under their oxidation conditions, these works clearly characterized the formation of an amorphous oxide layer.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…It was used to study nanocrystalline metal-oxide properties [16][17][18] or processes involved in the oxidation of metallic substrates [12,13,[19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33] Ogata and Campbell 31 and Campbell et al 32 have done the first variable charge MD simulations of oxidation of Al spherical nanoclusters where the thickness of the amorphous oxide film has been found to saturate at 3 to 4 nm. Gutierrez and Johansson 34 have investigated the structural properties of amorphous alumina ͑Al 2 O 3 ͒ using MD simulations with fixed atomic charges.…”
Section: Introductionmentioning
confidence: 99%